Traditional product rating in gastronomic circuits:: lessons from the Cerrado (Sustainability in Debate, 2015)
The social construction of differentiated and nested markets and alternative agrifood systems in relation to conventional agribusiness systems of modern agriculture constitute a significant strategy to overcome the exclusion of millions of small farmers and peasants. On its turn, the growing demand and differentiated use of traditional products in the gastronomic circuit, as well as new forms of interaction between chefs and farmers who produce traditional products, can be a drive for the construction of these differentiated markets. One of the findings of thisarticle is that the asymmetry between chefs and producers in the possession of symbolic capital necessary for the assessment process of the typical products has a negative impact for the distribution of economic capital and, as a result, there is great unevenness between the prices paid to produces and the prices of the dishes incorporating such products as delicacies. The appropriation of the economic result of the valuation decreases as a result of this process. The producer knowledge is often appropriated and reproduced in the assessment process and he does not take advantage of it. Departing from contributions of economic sociology and the economy of singularities, such issues are discussed by this article.